2012
DOI: 10.1007/s00253-012-4359-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of cytotoxicity induced by folic acid modified selenium nanoparticles in MCF-7 cells

Abstract: Selenium nanoparticles (Se NPs) have been recognized as promising materials for biomedical applications. To prepare Se NPs which contained cancer targeting methods and to clarify the cellular localization and cytotoxicity mechanisms of these Se NPs against cancer cells, folic acid protected/modified selenium nanoparticles (FA-Se NPs) were first prepared by a one-step method. Some morphologic and spectroscopic methods were obtained to prove the successfully formation of FA-Se NPs while free folate competitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 45 publications
1
32
0
1
Order By: Relevance
“…Atomic force microscopy is a useful tool for the collection of cellular surface information because it can detect the cellular topography, ultrastructure, and morphological changes [17, 18]. In this study, AFM was used to observe a variety of changes in the HUVEC surface morphology and ultrastructure in the different treatment groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force microscopy is a useful tool for the collection of cellular surface information because it can detect the cellular topography, ultrastructure, and morphological changes [17, 18]. In this study, AFM was used to observe a variety of changes in the HUVEC surface morphology and ultrastructure in the different treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…AFM is a powerful method that we can with which image cell surface ultrastructures under physiological conditions [29]. As a nondestructive surface imaging tool, AFM can obtain nanometric-scale images of the cell surface and can provide very important morphological and cell membrane details [18, 30]. Changes in cell morphology and pseudopod formation indicate the level of cell activity, and the cell surface particles indicate metabolic activity and functional protein secretion [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to stabilize the red selenium particles including the use of proteins (Kaur, Iqbal, & Bakshi, 2009;Shirazi et al, 2014;Xia, 2007), polyphenols (Barnaby, Sarker, Dowdell, & Bannerjee, 2011;Pi et al, 2013;Wu et al, 2013), polysaccharides (Kong et al, 2014;Soumya, Vineetha, Reshma, & Raghu, 2013;Zheng et al, 2013), melatonin , ATP , and monosaccharides (Zheng et al, 2011). These all have been used as dispersants to prepare stable and uniform selenium nanoparticles.…”
Section: Introductionmentioning
confidence: 97%
“…Over the past decade, much effort had been devoted to synthesize and stabilize SeNPs with the use of polysaccharides, 15,[18][19][20] monosaccharides, 21 proteins, 3,[22][23][24] amino acids, 25 polyphenols, [26][27][28] melatonin, 29 ATP, 30 complex plant extract 10,31 and even microorganism culture. 8 Among them, polysaccharide is regarded as an appropriate template for fabricating SeNPs when considering energy efficiency and eco-friendliness, according to Zhang et al 15 However, the SeNPs prepared using polysaccharides were found to be unstable, due to enlargement of size and decrease of zeta potential during storage in aqueous environment.…”
mentioning
confidence: 99%